A genetic algorithm-Taguchi based approach to inventory routing problem of a single perishable product with transshipment. (February 2017) - Azadeh, A.; Elahi, S.; Farahani, M. Hosseinabadi; Nasirian, B.
Highlights: A model of inventory routing with transshipment and single perishable product. Vehicle routing and inventory decisions are made simultaneously. A genetic algorithm based approach is presented to solve the NP-hard problem. Parameters are determined using Taguchi approach to achieve the best solution. An actual case is used to illustrate the validity of the model. Abstract: In this paper we present a model of inventory routing problem with transshipment in the presence of a single perishable product. In this problem, vehicle routing and inventory decisions are made simultaneously over the planning horizon to meet customer's demand under maximum level policy. Products are deteriorated at the exponential rate during the time they are stored in the depot or customer's warehouse. Due to the NP-hard nature of the model, we propose a genetic algorithm based approach to solve the problem. Moreover, the proposed algorithm parameters are determined using Taguchi design approach to achieve the best solution. Besides, a numerical example is used to illustrate the validity of the model. To the best of our knowledge, this is the first study that incorporates perishability of the products into inventory routing problem with transshipment, in which the products stocked in the depot or warehouses spoil due to their nature and also environmental issues.